PELATIHAN KEMAMPUAN BERBICARA DALAM BAHASA INGGRIS MASYARAKAT PESISIR PANTAI WINI PERBATASAN NKRI-RDTL - Edmundus Bouk; Desta Gloria Siahaan (Fakultas Teknik, Universitas Bangka Belitung, 2021)
The community service of the English Speaking Skills Training for the Wini Coastal Community at the NKRI-RDTL border was carried out by a service team, namely lecturers from the University of Timor. Wini Beach is located in North Insana District, North Central Timor Regency, East Nusa Tenggara. The training was held for 3 days at the Hamusu Wini Village Office and Wini Beach. The method used in this training is role play between the seller or guide and foreign tourist. The number of community service participants is 30 participants, coming from various backgrounds, with an age range of 7 - 29 years old. After the training, it can be concluded that the trainees are able to speak in Engl ish. The service also suggested that similar training could be carried out to improve the knowledge and fluency of the Wini coastal community in speaking English.